Degradation Degradasi Pewarna Tekstil Remazol Violet 5R Dengan Metode Elektrooksidasi Menggunakan Elektroda Grafit: Degradation of Remazol Violet 5R Textile Dyes with Electrooxidation Method Using Graphite Electrode - Suseno Suseno; Petrus Darmawan; Peni Pujiastuti; Sumardiyono Sumardiyono (LPPM Universitas Mataram, 2022)
Remazol Violet 5R textile dye degradation experiment has been carried out by electrooxidation method using graphite electrodes. The electrooxidation device consists of a plastic tub with a size (p x l x h) = 20 x 20 x 25 cm which is equipped with an electric stirrer and graphite electrodes using a used battery anode. Graphite electrodes consist of 3 pairs arranged in parallel. This dye degradation experiment was carried out using a batch system (not continuous) with variations in stirring time of 15, 30, 45, and 60 minutes, while the other variables were fixed, namely the concentration of dye 100.24 mg/liter, electrolyte NaCl 2.06 g/liter, 12 V voltage, and a stirring speed of 250 rpm. The dye solution before degradation and after degradation was measured for absorbance using a UV-Vis spectrophotometer at the maximum wavelength, to determine the percentage decrease in absorbance and optimum contact time. The experimental results showed that the percentage decrease in absorbance was constant after a contact time of 30 minutes with an absorbance of 98.36%. This indicates that the optimum contact time for the degradation of Remasol Violet 5R dye is 30 minutes. From the experiments that have been carried out, it can be concluded that the electrooxidation method using graphite electrodes can be used as an alternative waste treatment method, especially in terms of removing dyes in textile industry wastewater.